Varying abundance and dispersal of the two-spotted spider mite (Tetranychus urticae Koch, 1836, Acari: Prostigmata: Tetranychidae) on Mi-tomato plants differing in allelic combination - Godzina, Monika; Kiełkiewicz, Małgorzata; Szymczykiewicz, Katarzyna (Biological Letters, 2012)
It is well known that the presence of the Mi-1.2 gene determines the resistance of tomato plants (Solanum lycopersicum L.) to 3 root-knot nematode species and some insect herbivores of the order Hemiptera. In this study, the density and dispersal of two-spotted spider mites (Tetranychus urticae) on tomato plants of 4 cultivars were evaluated under greenhouse conditions, to find out whether tomatoes differing in allelic combination of the Mi-1.2 gene exhibit similar or different resistance to the mite pest. The results show, for the first time, that the same initial number of mites develops into populations that vary in abundance and distribution depending on tomato allelic composition of the Mi-1.2 gene. The results indicate that the mite-pest develops more slowly on tomato plants of cultivar ‘Motelle’, carrying 2 dominant alleles for the Mi-1.2 gene, than on heterozygous ‘Altess F1’ tomatoes and both cultivars carrying only recessive alleles of this gene: ‘Moneymaker’ and ‘Plaisence F1’. This suggests that the Mi-1.2 gene may be involved in tomato resistance against spider mites when this dominant gene is expressed homozygously, but this needs to be verified by further research.